Research and implement of file safe deposit box based on authentication and authorization - Xiao-ning DONG; Xiao-ping WU; Hong-cheng LI (网络与信息安全学报)
Considering that the existing file safe deposit boxes lack online authentication and server authorization,a file safe deposit box based on authentication and authorization was designed and achieved.This system firstly identified the users of the file box online,thus avoiding the illegal users to login.Moreover,the master collected the operation events exerted on the files in the clients,and the master provided a granular authentication for the operation of users,thus avoiding the illegal operation and incorrect operation.The test of this system proved that it can be able to achieve the preset functions and can be widely used in many conditions.